Rancang Bangun Sistem Informasi Perpustakaan pada SMA Dharma Wanita Surabaya - rahmadhani, zaki iga; Lusiani, Titik; Churniawan, Agus Dwi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
SMA Dharma Wanita surabaya is one of senior high school in Surabaya are also trying to improve the quality of education. One of the efforts is having facility library with good service. The Library was run by one staff. Limited have time staff library difficulty in doing the duties of them serving members and friendly and manage a collection of.Based on explanation above, then a library information system was built by. The library's web-based information systems can ease the task of library staff in providing information the catalog data. Members can view the transaction that is being done and suggest collection. This library information systems able to provide transaction reports quickly and can be accessed anywhere. The system can display collection suggestion data and visits conducted by members of the library. As admin staff can print a membership card and the card catalog.